Communicative musicality and sense of self (Orfeu, 2017)
This article presents a theoretical study about the following concepts: communicative musicality as proposed by Malloch (1999) and Malloch and Trevarthen (2009), and the sense of self put forward by Daniel Stern (1992-2000), with a purpose of   further understanding the nature of human beings’ relations with music. The strategy herein consists of establishing a conversation with a few researchers and articulating their ideas in order to understand the theme proposed. The conclusion asserts that   intersubjective relations form a common point that expresses both concepts. In communicative musicality, intersubjective relations are responsible for the emotional structure that guarantees shared musical experience; in forming the sense of self and its counterpart self with others, intersubjective relations create learning possibilities, including that of a musical sense of self or musical identity.
Keywords: Communicative musicality; Sense of self; Intersubjective processes